Aspects of psychosomatic disorders in highly qualified athletes - I. N. Mitin; A. E. Gorovaya; D. A. Kravchuk; O. R. Dobrushina; A. V. Zholinsky (National Electronic Information Consortium (NEICON), 2020)
Objective: to observe general abundance of various psychosomatic disorders among highly qualified athletes. Materials and methods: the study involved 3 094 athletes of Russian national teams with age range from 18 to 77 years. Analysis of data collected during the extend medical examinations (EME) of the national Russian team athletes in 2014-2016 years was conducted. Results: research shows high frequency of psychosomatic disorders among athletes of Russian national teams - 28,1%. The most common conditions among diseases with psychosomatic mechanisms in athletes of Russian national teams were disorders of the musculoskeletal system, the gastrointestinal tract, and the nervous system. Gender and age specific differences were shown. Conclusions: both psychological and psycho-physiological factors play significant role in the formation of psychosomatic disorders in athletes. Apparently, in view of the importance of social status (success) and, consequently, the tendency to negate problems, we expect late medical resource utilization in this group of the population (only in the case of a long and severe somatic disorder).